مكافحة تعذيب السجين في النظام السعودي والمواثيق الدولية، دراسة تاصيلية - هالة طالب, أبو عامر (University of Eloued جامعة الوادي, 2021)
تهدف هذه الدراسة إلى بيان مفهوم تعذيب السجين في الفقه الإسلامي والنظام السعودي والمواثيق الدولية، كما تهدف إلى بيان أركان هذه الجريمة وتشمل الركن المفترض والركن المادي والركن المعنوي، كما تتناول مظاهر الحماية الجنائية للسجين من التعذيب، حيث تطرقت إلى النصوص الواردة في الفقه الإسلامي والنظام السعودي والمواثيق الدولية التي تحظر تعذيب السجين، وتختتم هذه الدراسة بخاتمة تتضمن عدداً من النتائج والتوصيات . Abstract This study aims to clarify the concept of prisoner torture in Islamic jurisprudence, the Saudi law and international conventions. It also aims to clarify the pillars of this crime, including the presumed element, the material and the moral elements. It also deals with the aspects of criminal protection for prisoners from torture, as it touched upon the texts contained in Islamic jurisprudence and the Saudi Law and international covenants prohibiting prisoner torture, Finally the study concludes with a number of conclusions and recommendations.
Combating prisoner torture in Saudi law and international conventions Etymological Study
مقال
Keywords: مكافحة تعذيب السجين; prisoner, torture, the Saudi law, international conventions, Islamic jurisprudence